Process of infection with bacteriophage phi chi 174. XL. Viral DNA replication of phi chi 174 mutants blocked in progeny single-stranded DNA synthesis. - Fukuda, A (1976)
Mutation in several different cistrons of bacteriophage phi chi 174 blocks net progeny single-stranded DNA synthesis at the late period of infection (15). For the study of the functions of these cistrons in single-stranded DNA synthesis, asymmetric replication of replicative form DNA was examined at the late period of infection with amber mutants of these cistrons. While the normal, rapid process of asymmetric single-stranded viral DNA synthesis is blocked at the late period of these mutant infections, an asymmetric synthesis of the viral strand of replicative-form DNA is observed in this period, though at a reduced level, together with degradation of prelabeled viral strand. Some intermediate replicative-form molecules were also detected. Asymmetric synthesis of the viral strand of replicative-form DNA at the late period of phi chi infection is completely inhibited in the presence of a low concentration (35mug/ml) of chloramphenicol (which also blocks net single-stranded viral DNA synthesis). These results are discussed in terms of the possible role of the specific viral proteins for normal single-stranded DNA synthesis.